Societal preferences for funding orphan drugs in China: An application of the discrete choice experiment method - Tan, Shuoyuan; Wang, Yu; Tang, Yuqing; Jiang, Rong; Chen, Mingsheng; Chen, Haihong; Yang, Fan (Frontiers in Public Health, 2022)
Objectives To explore whether a societal preference for orphan drugs exists in Chinese general public and to quantitatively measure the personal trade-off between essential attributes of orphan drugs through a discrete choice experiment. Methods A labeled discrete choice experiment was employed to measure public preference. Six attributes (impact of diseases on life-years, impact of diseases on quality of life, availability of alternative drug treatments, annual cost per patient paid by medical insurance, expected increases in life-expectancy, and improvements to the quality of life) were identified through a literature review, experts' suggestions, and stakeholders' semi-structured interviews, then refined through a pre-survey. The current study used a D-efficient design to yield 27 choice sets divided into three blocks with nine questions containing the labeled treatment (either orphan drugs or common drugs). Information on sociodemographic characteristics and individual preferences was collected through a web-based questionnaire using convenience sampling. A mixed logit model was used to test societal preferences for orphan drugs over common drugs, while a binary logit model was used to measure the relative importance of each attribute in orphan drug access for the National Reimbursement Drug List and its willingness to pay. Results A total of 323 persons participated in this study. Respondents largely had indifferent attitudes toward orphan drugs and common drugs. The binary logit model results showed that 5 of the 6 attributes were significant, except for the availability of alternative drug treatments. The most impacted factor was the annual cost per patient paid by medical insurance (β = −1.734, odds ratio [OR] = 0.177). Among non-economic attributes, the impact of diseases on life-years—with no treatment, the patient will die in the prime of life (β = 0.523, OR = 1.688, willingness to pay = 301,895)—was most concerning, followed by significant improvements to the quality of life (β = 0.516, OR = 1.676, willingness to pay = 297,773). Conclusion The general public in China does not value rarity as a sufficient reason to justify special consideration in funding orphan drugs. When making orphan drug coverage decisions, the public prioritized the annual cost, disease severity, and drug effects.